Comparison of shear bond strength between unfilled resin to dry enamel and dentin bonding to moist and dry enamel - Yasini E.; Malekan E (Tehran University of Medical Sciences, 2005)
Statement of Problem: The use of dentine bondings on enamel and dentin in total etch protocols has recently become popular. Unfilled resin is hydrophobic and dentin bonding is hydrophilic in nature. This chemical difference could be effective in enamel bonding process. Purpose: The aim of this study was to compare the shear bond strength of unfilled resin to dry enamel and dentin bonding to dry and moist enamel. Materials and Methods: In this experimental study, a total of 30 incisor teeth were used. The specimens were randomly assigned to three groups of 10. 37% phosphoric acid etchant was applied to the enamel surfaces in each group for 15 seconds, rinsed with water for 20 seconds and dried for 20 seconds with compressed air in groups one and two. After conditioning, group 1 received unfilled resin (Margin Bond, Colten) and group 2 received dentin bonding (Single Bond, 3M) and in group 3 after conditioning and rinsing with water, a layer of dentin bonding (Single Bond) was applied on wet enamel. The enamel and dentin bonding were light cured for 20 seconds. A ring mold 3.5 mm in diameter and 2 mm height was placed over the specimens to receive the composite filling material (Z100, 3M). The composite was cured for 40 seconds. The specimens were thermocycled and shear bond strengths were determined using an Instron Universal Testing Machine. The findings were analyzed by ANOVA One-Way and Tukey HSD tests. Results: Shear bond strength of dentin bonding to dry enamel was significantly less than unfilled resin to dry enamel (P<0.05). There was no significant difference between the bond strength of dentin bonding to moist and dry enamel. In addition bond strength of dentin bonding to wet enamel was not significantly different from unfilled resin to dry enamel. Conclusion: Based on the findings of this study, it is suggested that enamel surface should remain slightly moist after etching before bonding with single bond but when using unfilled resin, the enamel surface should be kept dry.